HUBUNGAN ANTARA DUKUNGAN SOSIAL DENGAN KEMANDIRIAN PADA PENYANDANG TUNA DAKSA DI PUSAT REHABILITASI TERPADU PENYANDANG CACAT BANTUL - Vira Rachmiwanti; Hartosujono Hartosujono (JURNAL SPIRITS, 2015)
Abstract This research aimed to find out to the correlation between social support with physically disabled in the Physically disabled rehabilitation center, to know the significant of social support function to autonomy of individual.The research was held in Physically disabled rehabilitation which subject were taken from 18 -35 years old of 120 people of physically disabled. To gain the data, the researcher used questionnaire method. The sample is taking with the purposive sample. Product moment Correlation analysis method was applied to analyze the data and it reached 5% of significance.The result of the data analysis showed that the social support  had a significance effect to the autonomy individual  with the value of r =0,399, (p>0,05), also give significant effect to it. Adjusted value (R2) of 0,159 means that 15,9% of variation of autonomy individual could be explained with the variation of social support. Meanwhile, 84,1% was caused by other factors. Keywords: social support and self-reliance